Operational Risk Management in the Reverse Logistics Process of Used Vehicle Oil - Paredes-Rodríguez, Andrés-Mauricio; Grisales-Aguirre, Andrés-Felipe; Sánchez-Zambrano, David-Alberto (Revista Facultad de Ingeniería, 2022)
Currently, supply chains seek to establish strategies for the recovery and reincorporation of products that reach the end of their useful life. However, in these reverse logistics operations, certain events might generate financial losses for the company and adverse effects harmful to the environment and the community. In this paper, an identification, prioritization and control process is carried out for the most representative operational risks in the reverse logistics process of used vehicle oil. There is a high volume of this waste generated within the country, and poor management of the activities of recovery can generate environmental, economic, and social problems. The methodology used for the risk management process involves using the fuzzy QFD multi-criteria tool to evaluate the most common operational events within the process using the assessment of experts in the sector. Subsequently, a series of mitigation strategies are designed using the Ishikawa diagram. Among the most relevant results found in the study is the fact that the most relevant risks in the reverse logistics of used vehicle oil are the inadequate storage process, the absence of an adequate vehicle for transport, and the low quality of the waste. The research carried out establishes a reference framework for the risk management process in companies dedicated to the use and reuse of products in a closed-loop supply chain.